The C-terminus of Bienertia sinuspersici Toc159 contains essential elements for its targeting and anchorage to the chloroplast outer membrane - Lung, Shiu-Cheung; Smith, Matthew D.; Weston, J. Kyle; Gwynne, William; Secord, Nathan; Chuong, Simon D. X. (Frontiers in Plant Science, 2014)
Most nucleus-encoded chloroplast proteins rely on an N-terminal transit peptide (TP) as a post-translational sorting signal for directing them to the organelle. Although Toc159 is known to be a receptor for specific preprotein TPs at the chloroplast surface, the mechanism for its own targeting and integration into the chloroplast outer membrane is not completely understood. In a previous study, we identified a novel TP-like sorting signal at the C-terminus (CT) of a Toc159 homolog from the single-cell C4 species, Bienertia sinuspersici. In the current study, we have extended our understanding of the sorting signal using transient expression of fluorescently-tagged fusion proteins of variable-length, and with truncated and swapped versions of the CT. As was shown in the earlier study, the 56 residues of the CT contain crucial sorting information for reversible interaction of the receptor with the chloroplast envelope. Extension of this region to 100 residues in the current study stabilized the interaction via membrane integration, as demonstrated by more prominent plastid-associated signals and resistance of the fusion protein to alkaline extraction. Despite a high degree of sequence similarity, the plastid localization signals of the equivalent CT regions of A. thaliana Toc159 homologs were not as strong as that of the B. sinuspersici counterparts. Together with computational and circular dichroism analyses of the CT domain structures, our data provide insights into the critical elements of the C-terminus for the efficient targeting and anchorage of Toc159 receptors to the dimorphic chloroplasts in the single-cell C4 species.